Animal cumulative culture through changing environments - Bradley D. Ohlinger; Josep Call; Mathieu Charbonneau; Takao Sasaki (Trends in Ecology & Evolution, 2026)

Orang-utans and chimpanzees cooperate strategically based on the partner’s incentives - Christoph J. Völter; Elisa Felsche; Josep Call; Federico Rossano (Animal Behaviour, 2026)

Do chimpanzees produce context-specific vocal structures in group-specific ways? - Adrian Soldati; Katie Slocombe; Josep Call; Klaus Zuberbühler; Erik P. Willems; Pawel Fedurek (Animal Behaviour, 2025)

Training primates to forage in virtual 3D environments - Emma Suvi McEwen; Matthias Allritz; Josep Call; Sarah E. Koopman; Emilie Rapport Munro; Cristóbal J. Bottero Cantuarias; Charles R. Menzel; Francine L. Dolins; Karline R.L. Janmaat; Kenneth Schweller (Behavioural Processes, 2025)

The Ontogeny of Vocal Sequences: Insights from a Newborn Wild Chimpanzee (Pan troglodytes schweinfurthii) - Adrian Soldati; Geresomu Muhumuza; Guillaume Dezecache; Pawel Fedurek; Derry Taylor; Josep Call; Klaus Zuberbühler (International Journal of Primatology, 2023)
Observations of early vocal behaviours in non-human primates (hereafter primates) are important for direct comparisons between human and primate vocal development. However, direct observations of births and perinatal behaviour in wild primates are rare, and the initial stages of behavioural ontogeny usually remain undocumented. Here, we report direct observations of the birth of a wild chimpanzee ( Pan troglodytes schweinfurthii ) in Budongo Forest, Uganda, including the behaviour of the mother and other group members. We monitored the newborn’s vocal behaviour for approximately 2 hours and recorded 70 calls. We categorised the vocalisations both qualitatively, using conventional call descriptions, and quantitatively, using cluster and discriminant acoustic analyses. We found evidence for acoustically distinct vocal units, produced both in isolation and in combination, including sequences akin to adult pant hoots, a vocal utterance regarded as the most complex vocal signal produced by this species. We concluded that chimpanzees possess the capacity to produce vocal sequences composed of different call types from birth, albeit in rudimentary forms. Our observations are in line with the idea that primate vocal repertoires are largely present from birth, with fine acoustic structures undergoing ontogenetic processes. Our study provides rare and valuable empirical data on perinatal behaviours in wild primates.

Raising the level: orangutans solve the floating peanut task without visual feedback - Carla Sebastián-Enesco; Nerea Amezcua-Valmala; Fernando Colmenares; Natacha Mendes; Josep Call (Primates, 2022)
Chimpanzees and orangutans are able to generate innovative behaviors to solve complicated physical problems. For example, when presented with an out-of-reach peanut at the bottom of a vertical tube (floating peanut task—FPT), some of them spontaneously spit water into the tube until the peanut floats to the top. Yet, it is unclear whether this innovative solution results from repeating those actions that bring the peanut incrementally closer to the top or from anticipating the solution before acting. In the current study, we addressed this question by presenting three naïve orangutans with an opaque version of the FPT that prevented them from obtaining visual information about the effect of their actions on the position of the peanut. One of the subjects solved the opaque FPT in the very first trial: he collected water from the faucet and poured it into the opaque tube repeatedly until the hitherto non-visible peanut reached the top. This provides evidence for the first time that orangutans can potentially solve the FPT without relying on sensorimotor learning, but to some extent by mentally representing the problem.

Quantitative cognition in carpenter ants - Patrizia d’Ettorre; Patricia Meunier; Pietro Simonelli; Josep Call (Behavioral Ecology and Sociobiology, 2021)

Effects of indirect reputation and type of rearing on food choices in chimpanzees (Pan troglodytes) - Nereida Bueno-Guerra; Montserrat Colell; Josep Call (Behavioral Ecology and Sociobiology, 2020)

Chimpanzees use observed temporal directionality to learn novel causal relations - Claudio Tennie; Christoph J. Völter; Victoria Vonau; Daniel Hanus; Josep Call; Michael Tomasello (Primates, 2019)
We investigated whether chimpanzees use the temporal sequence of external events to determine causation. Seventeen chimpanzees ( Pan troglodytes ) witnessed a human experimenter press a button in two different conditions. When she pressed the “causal button” the delivery of juice and a sound immediately followed (cause-then-effect). In contrast, she pressed the “non-causal button” only after the delivery of juice and sound (effect-then-cause). When given the opportunity to produce the desired juice delivery themselves, the chimpanzees preferentially pressed the causal button, i.e., the one that preceded the effect. Importantly, they did so in their first test trial and even though both buttons were equally associated with juice delivery. This outcome suggests that chimpanzees, like human children, do not rely solely on their own actions to make use of novel causal relations, but they can learn causal sequences based on observation alone. We discuss these findings in relation to the literature on causal inferences as well as associative learning.

Calculated reciprocity? A comparative test with six primate species - Federica Amici; Filippo Aureli; Roger Mundry; Alejandro Sánchez Amaro; Abraham Mesa Barroso; Jessica Ferretti; Josep Call (Primates, 2014)

Response facilitation in the four great apes: is there a role for empathy? - Federica Amici; Filippo Aureli; Josep Call (Primates, 2014)

Food washing and placer mining in captive great apes - Matthias Allritz; Claudio Tennie; Josep Call (Primates, 2013)

Leaf Surface Roughness Elicits Leaf Swallowing Behavior in Captive Chimpanzees (Pan troglodytes) and Bonobos (P. paniscus), but not in Gorillas (Gorilla gorilla) or Orangutans (Pongo abelii) - Claudia Menzel; Andrew Fowler; Claudio Tennie; Josep Call (International Journal of Primatology, 2013)

What Role Do Mothers Play in the Gestural Acquisition of Bonobos (Pan paniscus) and Chimpanzees (Pan troglodytes)? - Christel Schneider; Josep Call; Katja Liebal (International Journal of Primatology, 2012)

Two-year-old children copy more reliably and more often than nonhuman great apes in multiple observational learning tasks - Claudio Tennie; Kathrin Greve; Heinz Gretscher; Josep Call (Primates, 2010)

Do bonobos say NO by shaking their head? - Christel Schneider; Josep Call; Katja Liebal (Primates, 2010)

Superior olivary complex organization and cytoarchitecture may be correlated with function and catarrhine primate phylogeny - Heidegard Hilbig; Boris Beil; Henrik Hilbig; Josep Call; Hans-Jürgen Bidmon (Brain Structure and Function, 2009)

Sumatran Orangutans and a Yellow-Cheeked Crested Gibbon Know What Is Where - Marina Scheumann; Josep Call (International Journal of Primatology, 2006)

The effect of inter-opponent distance on the occurrence of reconciliation in stumptail (Macaca arctoides) and rhesus macaques (Macaca mulatta) - Josep Call (Primates, 1999)